Women-friendly Response to Violence Against Women - 4 day Demonstration Training Seminar - Duluth model - Part 11/12
The Demonstration Training Seminar was organized by the Network Women’s Program of OSI at the CEU Conference Center in Budapest, Hungary. Date of Seminar: 25-28 November 1998. Participating Countries of the OSI Network: Albania, Armenia, Bulgaria, Croatia, Estonia, Hungary, Kyrgyzstan, Latvia, Lithuania, Macedonia, Moldova, Mongolia, Romania, Russia, Slovak Republic, Slovenia, Turkmenistan, Ukraine and Yugoslavia. Training partner: The Duluth Domestic Abuse Intervention Project (DAIB) Date of Recording: Nov. 1998